The current status of the sustainable development goals in the world - Edith Johana Medina-Hernández; Diana Sirley Guzmán-Aguilar; Jorge Luis Muñiz-Olite; Luis Ricardo Siado-Castañeda (Development Studies Research, 2023)
ABSTRACTSustainable development goals (SDG) incorporate multiple dimensions to measure the progress made by nations in consolidating their economic and human development. Consequently, the main objective of this study is to explore the structures of variation and covariation between the SDGs indicators interpreting and describing their current status by countries and regions of the world. This study assessed 40 SDG indicators reported by 125 countries in the 2021 Sustainable Development Report, using the HJ-Biplot multivariate technique, through which it is possible to analyze the existing relationships between indicators and countries in a multidimensional way. The results indicate that the global North countries currently display solid sustainability characteristics that favor economic growth, though more work is required to protect the environment and promote responsible production and consumption. On the other hand, the countries of the global South with less purchasing power must still work on policies and strategies to promote the health and well-being of their populations, enable access to essential household services (water, sanitation, electricity, and internet, among others), and promote equality.